Evolution of Gas Permeable Membranes for Extracorporeal Membrane Oxygenation. Issue 8 (19th January 2017) - Yeager, Torin; Roy, Shuvo
Abstract: Gas permeable membranes are a vital component of extracorporeal membrane oxygenation systems. Over more than half a century, membrane fabrication and packaging technology have progressed to enable safer and longer duration use of respiratory life support. Current research efforts seek to improve membrane efficiency and hemocompatibility, with the aim of producing smaller and more robust systems for ambulatory use. This review explores past and present innovations in oxygenator technology, suggesting possible applications of state‐of‐the‐art membrane fabrication methods to address shortcomings of earlier concepts.